LASER MYRINGOTOMY VERSUS VENTILATION TUBES IN OTITIS MEDIA WITH EFFUSION - Yousaf, Mohammad; Malik, Suhail Ahmad; Haroon, Tahir (Journal of Ayub Medical College Abbottabad, 2016)
Background: Otitis media with effusion (OME) is a leading cause of difficulty in hearing in paediatric population. Otitis media with effusion must be detected and managed early to prevent conductive hearing loss in children. It was aimed to compare results of laser myringotomy and ventilation tube insertion, in terms of hearing improvement and recurrence of Middle ear effusion (MEE). Methods: This randomized controlled trial was conducted from February 2012 to January 2015. Children of 4- 12 years of age with decreased hearing due to OME were included in the study. These children were investigated with pure tone audiometry (PTA) and tympanometry to confirm conductive hearing loss. Patients were put in 2 groups, group one comprised of patients treated with laser myringotomy and group 2, treated with ventilation tube insertion. The objective was to evaluate and compare results of the two procedures in terms of resolution of middle ear effusion (MEE) and improvement of hearing. The two procedures were also compared in terms of complications like otorrhea, persistence of perforation, hypertrophic scar and thinning of tympanic membrane (TM). Results: Middle ear effusion cleared in 35 out of 68 ears with laser myringotomy (LM) as compared to 52 out of 62 ears with ventilation tubes (VT). The myringotomy was still patent in 21 ears treated with LM while tube was in site in 50 years with VT after 3 months. The hearing level improved with LM by 10-15 dB after first 3 months. Conclusion: The aim in Otitis media with effusion is ventilation of tympanic cavity. Laser myringotomy can be substitute to ventilation tube insertion (VT). But it remains patent for shorter time and less effective than VT. The ears with refractory or recurrent MEE should have VT insertion. Keywords: Otitis media with effusion; Middle ear effusion; Laser myringotomy; Ventilation tubes; Tympanometry